ROLE OF THE ANTERIOR CINGULATE AND MEDIAL ORBITOFRONTAL CORTEX IN PROCESSING DRUG CUES IN COCAINE ADDICTION - Goldstein, Rita Z. (2006)
Our goal in the current report was to design a new fMRI task to probe the role of the anterior cingulate cortex (ACC) and orbitofrontal cortex (OFC) in processing of salient symptom-related cues during the simultaneous performance of an unrelated task in drug addicted individuals. We used a novel functional magnetic resonance imaging color-word drug Stroop task in 14 individuals with cocaine use disorders; subjects had to press for color of drug vs. matched neutral words. Although there were no accuracy or speed differences between the drug and neutral conditions in the current sample of subjects, drug words were more negatively valenced than the matched neutral words. Further, consistent with prior reports in individuals with other psychopathologies using different Stroop fMRI paradigms, our more classical color-word Stroop design revealed bilateral activations in the caudal-dorsal ACC (cdACC) and hypoactivations in the rostro-ventral ACC/medial OFC (rACC/mOFC). A trend for larger rACC/mOFC hypoactivations to the drug than neutral words did not survive whole-brain corrections. Nevertheless, correlation analyses indicated that (1) the more the cdACC drug-related activation, the more negative the valence attributed to the drug words (r=-0.86, p < 0.0001) but not neutral words; and (2) the more the rACC/mOFC hypoactivation to drug minus neutral words, the more the errors committed specifically to the drug minus neutral words (r=0.85, p < 0.0001). Taken together, results suggest that this newly developed drug Stroop fMRI task may be a sensitive biobehavioral assay of the functions recruited for the regulation of responses to salient symptom-related stimuli in drug addicted individuals.